Internalization of character education in social studies learning at junior high school - Khotimah, Kusnul (Jurnal Teori dan Praksis Pembelajaran IPS, 2025)
To support effective learning, character-based learning support is needed. This study aims to analyze the internalization of character education in social studies learning in three schools in the suburban of Surabaya. A qualitative method with a case study approach was used for this study. Principals, social studies teachers, students, and parents were involved as informants. Data collection was carried out through in-depth interviews with informants, observations in the school environment, and analysis of documents owned by teachers and schools. The results of this study found that the process of internalizing character education was designed by teachers in the learning planning in the teaching module, the implementation of learning in the classroom, and the evaluation carried out after learning. Some social studies teachers were able to implement the process of internalizing education in the learning planning in the teaching module, but there were also teachers who were unable to integrate it into the learning planning in their teaching module. Meanwhile, in terms of implementation, some teachers failed to integrate character education into the learning process, despite having written it in the teaching module. During formative evaluation, teachers were able to develop formative questions that integrated character education. Furthermore, there was collaboration with parents, although not always optimal. The main findings indicate that students who experience learning loss in elementary school will carry it into junior high school, thereby reducing the quality of their character. This research recommends strengthening the capacity of social studies teachers to internalize character education in their learning. Furthermore, schools must receive support from parents and the surrounding community.